Фактори формування гнучкості промислових підприємств України - Шматько, Наталія Михайлівна (НТУ "ХПІ", 2016)
Розглянуто та розкрито поняття гнучкості промислового підприємства, порівняно поняття гнучкості та адаптивності промислового підприємства України, тому що існуюча класифікація розкриває лише довгострокові аспекти гнучкості промислового підприємства, залишаючи поза увагою гнучкість як можливість термінової зміни. Таким чином запропонована нова класифікаційна ознака гнучкості – форма прояву, за якою виділити три її види: результативна, процесна і потенційна (потенціал гнучкості).

The concept considered and flexibility of an industrial enterprise. Compared to the concept of flexibility and adaptability of the industrial enterprises of Ukraine. The current classification reveals only the long-term aspects of industrial enterprise flexibility, leaving aside the possibility of flexibility as urgent change. For example, the setup of the production system to produce a product that is not new to the company. We offer flexibility and extend the classification of the enterprise by driving a new kind of flexibility - operational. Operational flexibility to allow for short-term flexibility aspects of the companies that do not require fundamental changes. A new classification sign of flexibility - a form of manifestation at which it divided into three types: productive, process and potential (potential flexibility).
Keywords: адаптивність; конкурентоспроможність підприємства; класифікація; потенціал промислового підприємства; adaptability; competitiveness of the enterprise; classification